The burden of Clostridioides difficile infection in COVID-19 patients: A systematic review and meta-analysis. (April 2022) - Granata, Guido; Petrosillo, Nicola; Al Moghazi, Samir; Caraffa, Emanuela; Puro, Vincenzo; Tillotson, Glenn; Cataldo, Maria Adriana
Abstract: Objectives: The main aim of this systematic review and meta-analysis was to assess the proportion of confirmed COVID-19 patients with Clostridioides difficile infection (CDI) and to describe risk factors and outcome of these patients. Methods: MEDLINE and Cochrane Central Register of Controlled Trials databases were searched up to July 15, 2021. We included studies reporting data on CDI occurring in patients with a confirmed diagnosis of COVID-19. We pooled proportion of CDI patients using a random effects model (DerSimonian–Laird method) stabilising the variances using the Freeman-Tukey double arcsine transformation. Results: Thirteen studies were included in the systematic review. All the studies retrospectively collected data between February 2020 and February 2021. The reported CDI incidence rates ranged from 1.4 to 4.4 CDI cases per 10, 000 patient-days. Seven studies reported data on the number of COVID-19 patients who developed CDI and the total number of COVID-19 patients in the study period and were included in the meta-analysis, comprising 23, 697 COVID-19 patients. The overall pooled proportion of COVID-19 patients who had CDI was 1% [95% confidence interval: 1–2]. Among studies reporting CDI occurrence in patients with and without COVID-19, the majority of them reported reduced or unchanged CDI rates compared to pre-COVID period. Conclusions: CDI is a relevant issue for COVID-19 patients. Adherence to infection prevention and control measures and to the antimicrobial stewardship principles is crucial even during the COVID-19 pandemic. Highlights: Data on the prevalence, on the risk factors and on the outcome of CDI in COVID-19 patients are scant. In our systematic review, the reported CDI incidence rates ranged from 1.4 to 4.4 CDI cases per 10, 000 patient-days. The meta-analysis included 7 studies on the number of COVID-19 patients who developed CDI, for a total of 23, 697 COVID-19 patients. The overall pooled proportion of COVID-19 patients who had CDI was 1% [95% confidence interval: 1 - 2]. These findings highlight that CDI is a relevant issue for COVID-19 patients. Infection prevention and control measures and antimicrobial stewardship are more important than ever during the COVID-19 pandemic.